Analysis of ultra-low uncertainty gas turbine flow capacity measurement techniques - Burdett, D; Hambidge, C; Povey, T (SAGE Publications, 2020)
Accurate assessment of nozzle guide vane (NGV) capacity is essential for understanding engine performance data, and to achieve accurate turbine stage matching. In accelerated engine development programmes in particular, accurate and early assessment of NGV capacity is a significant advantage. Whilst the capabilities of computational methods have improved rapidly in recent years, the accuracy of absolute capacity prediction capability is lower than experimental techniques by some margin. Thus, experimental measurement of NGV capacity is still regarded as an essential part of many engine programmes. The semi-transient capacity measurement technique, developed and refined at the University of Oxford over the last 10 years, allows rapid and accurate measurement of engine component (typically fully cooled NGVs) capacity at engine-representative conditions of Mach and Reynolds numbers and coolant-to-mainstream pressure ratio. The technique has been demonstrated to offer considerable advantages over traditional (industrial steady-state) techniques in terms of accuracy, time and operating cost. Since the original facility was constructed, the facility has been modularised to allow for rapid interchange of test vane modules, and the instrumentation has been optimised to drive down the uncertainty in NGV capacity. In this paper, these improvements are described in detail, and a detailed uncertainty analysis is presented of the original facility, the current facility, and a proposed future facility in which the uncertainty of the measurement has been driven down to a practical limit. The bias errors of the three facilities are determined to be ±0.535%, ± 0.495% and ±0.301%, respectively (to 95% confidence). The corresponding precision uncertainties are ±0.028%, ±0.025% and ±0.025%, respectively. The extremely low precision uncertainty in particular allows very small changes in capacity to be resolved. This, combined with rapid interchangeability of test modules, allows studies of the sensitivity of capacity to secondary influences with much greater flexibility than was previously possible. Consideration is also given to the definition of vane capacity in systems with several streams at different conditions of inlet total pressure and temperature. A typical high pressure (HP) NGV has three distinct streams: a mainstream flow; coolant flow ejected from film cooling holes (distributed over the vane surface); and trailing edge coolant ejection. Whilst it is helpful for the coolant mass flow rates and inlet temperatures to be included in the definition, only a relatively small difference arises from the way in which this is achieved. Several definitions appear to share similar usefulness in terms of their robustness to changing inlet conditions of individual streams, but the favoured definition offers the possibility of isolating sensitivities to key effects such as trailing edge coolant ejection. This is achieved by explicitly expressing vane capacity as a function of two controlling pressure ratios. The overall purpose of this paper is to review and analyse in detail the current state-of-the-art in gas turbine flow capacity measurement.